Magnitude of syphilis sero-status and associated factors among pregnant women attending antenatal care in Jinka town public health facilities, Southern Ethiopia, 2020 - Enbiale, Mulusew; Getie, Asmare; Haile, Frehiwot; Tekabe, Beemnet; Misekir, Direslgn (PloS one, 2021)
Syphilis is one of the leading causes of perinatal morbidity and mortality and is one of the most important public health problems. There was no study showing syphilis serostatus and its related factors among pregnant women in the current study area. This study was aimed to assess the magnitude of syphilis serostatus and associated factors among pregnant women attending antenatal care in Jinka town public health facilities. Institution based cross-sectional study design was conducted in Jinka town public health facilities, southern Ethiopia from the 1st July to the 1st September, 2020. A systematic sampling technique was used to select 629 study subjects. Data were collected using a structured questionnaire through face-to-face interviews and records were reviewed to check syphilis test results. Data were coded and entered by using Epi-data version 4.432 and analyzed using SPSS version 25. The binary logistic regression model was used to investigate factors associated with syphilis. A p-value of < 0.05 at multivariable analysis was considered statistically significant. In this study, syphilis sero-prevalence among pregnant women attending antenatal care clinics was 4.8% (95% CI: 3.12, 6.48). Rural residence [AOR: 2.873; 95%CI (1.171, 7.050)], alcohol use [AOR: 3.340; 95% CI (1.354, 8.241)] and having multiple sexual partner [AOR: 5.012; 95% CI (1.929, 13.020)] were statistically significantly associated with syphilis. Sero-prevalence of syphilis was high. Being a rural residence, having multiple sexual partners, alcohol use were factors associated with syphilis. Therefore, substantial efforts have to be made to provide regular health education for pregnant women at the antenatal clinic on the avoidance of risky behaviors and the risk of syphilis on their pregnancy.